Pengaruh Pelaporan Terintegrasi Terhadap Kualitas Laba Dengan Biaya Keagenan Sebagai Pemoderasi - Katarina Alvina; Hendra Wijaya (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2021)
Integrated reporting combines information about company's governance, performance, strategy, and future prospects that reflect the company's activities. As the voluntary integrated reporting practice increases, the global issue related to that is about the integrated reporting’s future implications, particularly the accounting information. In Indonesia, companies that are ready for integrated reporting are the winners the Sustainability Reporting Awards (SRA). Implementation of integrated reporting can improve earnings quality. This research is to provide evidence for the effect of integrated reporting on earnings quality and the moderating effect agency costs in it. The research design is a quantitative research using secondary data sources from company’s annual reports. The research object are Indonesian non-financial sector companies that are winners and non-winners of the 2015-2019 SRA which are registered in the IDX fact book 2019. This research used a moderation regression analysis model. The research contributed to three new findings: (a) integrated reporting has no effect on earnings quality; (b) agency costs weaken the effect of integrated reporting on earnings quality in non-financial sector companies; and (c) agency costs strengthen the effect of integrated reporting on earnings quality in SRA companies.